(untitled) (Al-Mansour Journal, 2023)
Modeling procedure is proposed to determine impulsive tensile response of a flexible composite of polymer base (resin) and sine-shaped glass fibers. A certain elastic model is adopted and developed in order to determine important mechanical parameters to be used in impulsive response determination in the present procedure.